2020
DOI: 10.1136/bmjdrc-2019-001128
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reversal of diabetes by subcutaneous transplantation of pancreatic islet cells and adipose-derived stem cell sheet using surface-immobilized heparin and engineered collagen scaffold

Abstract: ObjectiveEsterified collagen (EC) can be functionalized with heparin to enhance islet graft stability. Growth factors secreted by human adipose-derived stem cells (hADSCs) can bind efficiently to EC-heparin (EC-Hep), which enhances revascularization and cell protection. We investigated the therapeutic potential of a combined heparin-esterified collagen-hADSC (HCA)-islet sheet to enhance islet engraftment.Research design and methodsThis study was designed to assess the efficiency of using EC-Hep as a scaffold f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Arguably, though the duration of glycemic correction in for the in vivo study might be considered relatively short, this data were sufficient to demonstrate that the alginate‐coated WIM device has adequately shielded the transplanted rat islets from destruction by the immune system of diabetic mice during this period of time. Specifically, if the rat islets were not sufficiently protected from the immune system of immunocompetent diabetic mice, islet death would have occured within the first few days resulting in immediate loss of blood glucose control as observed in published studies 48,49 . Furthermore, it is important to highlight that the duration of glycemic correction depends on multiple factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Arguably, though the duration of glycemic correction in for the in vivo study might be considered relatively short, this data were sufficient to demonstrate that the alginate‐coated WIM device has adequately shielded the transplanted rat islets from destruction by the immune system of diabetic mice during this period of time. Specifically, if the rat islets were not sufficiently protected from the immune system of immunocompetent diabetic mice, islet death would have occured within the first few days resulting in immediate loss of blood glucose control as observed in published studies 48,49 . Furthermore, it is important to highlight that the duration of glycemic correction depends on multiple factors.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, if the rat islets were not sufficiently protected from the immune system of immunocompetent diabetic mice, islet death would have occured within the first few days resulting in immediate loss of blood glucose control as observed in published studies. 48 , 49 Furthermore, it is important to highlight that the duration of glycemic correction depends on multiple factors. Specifically, comparing duration of glycemic control for different device designs requires standardization of therapeutic dosage, the partial oxygen pressure at the implant site and the presence of any enhancing factor such as oxygen‐generating materials or supporting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow is highly vascularized but requires pre-conditioning before it can be considered for islet transplantation. ,000 rat IEQ and 8,000 human IEQ Esterified collagen scaffold functionalized with heparin contained varying number human adipose-derived stem cells and islets, transplanted subcutaneously Higher number of human adipose-derived stem cells resulted in normoglycemia within 1 day posttransplantation, and maintained for up to 100 days (84) Murine, porcine and human islets and cynomolgus islets (autotransplantation)…”
Section: Liver Transplantation Sitementioning
confidence: 99%
“…Using syngeneic, as well as immune-compromised mouse models of T1D, they showed that normoglycemia could be achieved in 91% of the mice for over 100 days using islets from both mice and humans. In contrast, Kim et al on the other hand used esterified collagen along with heparin and hADSCs for their islet transplantation into the subcutaneous space of NOD mice (84) and found that this system improves normoglycemia better than with native collagen alone. Interestingly, they also showed that this effect is dosage-dependent on hADSCs, indicating that hADSCs or factors secreted by hADSCs is a contributing factor to survival and vascularization of transplanted islets.…”
Section: Subcutaneous Space Transplantation Sitementioning
confidence: 99%
“… 52 However, other studies reported successful subcutaneous transplantation of pancreatic islets admixed with a device-free islet viability matrix. 55 , 56 Of course these approaches are at present time only hypothetical because data available are still limited and no large animal model of diabetes is rendered insulin independent with this approach. The omentum was evaluated in preclinical studies since it associates different physical characteristics such as the vastness of the surface and the great vascularity.…”
Section: Pancreas and Islet Transplantationmentioning
confidence: 99%